Cyber witchcraft and financial extortion of women in Libyan society: A sociological study of the influential social and cultural factors (Al-Farooq Journal of Sciences, 2026)
This paper aims to shed light on the growing phenomenon of women in Libya believing in online sorcerers and charlatans, and the resulting planned financial extortion. The findings indicate that this phenomenon is on the rise, driven by weak religious awareness, low digital literacy, increasing family and psychological problems, as well as the influence of social traditions and the weakness of awareness and legal protection systems. Official statistics show a yearly increase in reported cases, rising from 47 cases in 2020 to 136 cases in 2024, with the upward trend continuing into 2025. The majority of victims are women aged 25–45, and the extortion process often begins with a promise to solve a personal or family problem, then escalates to threats of publishing private information or photos if the victim refuses to pay more money. Despite the enactment of Law No. 6 of 2024, which imposed stricter penalties on sorcery, witchcraft, and extortion crimes, practical challenges remain, especially regarding the difficulty of digital evidence and victims’ reluctance to report due to fear of social stigma. There is a clear need for ongoing religious and digital awareness campaigns, the development of effective reporting and protection mechanisms, and the involvement of civil society, security, and religious institutions in combating this phenomenon and protecting women from digital exploitation and financial blackmail.
Keywords: Digital sorcery, online witchcraft, financial extortion, women in Libya, weak religious awareness, cybercrime, religious awareness, Libyan legislation, legal protection, social traditions